Analysis of Key Variables for the Sustainability of the Simantri Program in Tabanan District - Lestari, Desak Putu Diah Merta; Ayu Nyoman Saskara, Ida; Wiwin Setyari, Ni Putu (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
Empowering farmers through the implementation of the Simantri Program is one of the regional agricultural development policies in Bali Province. The program aims to achieve long-term self-sufficiency in food, feed, organic fertilizer, energy (biogas), and farmer welfare. This study focuses on identifying the important variables that contribute to the sustainability of the Simantri program, with the research conducted in Tabanan Regency. The identification of key variables was done through a Focus Group Discussion (FGD) involving 19 stakeholders, and a questionnaire was also used to gather data from Gapoktan as a control measure for the FGD results. The collected data was analyzed using the MICMAC (Matrix of Cross Impact Multiplications Applied to a Classification) method to determine the variables that influence and/or depend on the sustainability of the Simantri Program. The analysis results revealed several crucial variables out of the 13 identified, namely seed assistance, fertilizer prices, natural capital, customary regulations, and local wisdom, all of which significantly impact the sustainability of the Simantri program.